Second Degree Refinement Jacobi Iteration Method for Solving System of Linear Equation - Tesfaye Kebede (LPPM Institut Teknologi Sepuluh Nopember, 2017)
Several iterative techniques for the solution of linear system of equations have been proposed in different literature in the past.In this paper, we present a Second degree of refinement Jacobi Iteration method for solving system of linear equation, Ax = b and we consider few numerical examples and spectral radius to show that the effective of the Second degree of refinement Jacobi Iteration Method (SDRJ) in comparison with other methods of First degree Jacobi (FDJ), First degree Refinement Jacobi (FDRJ) and Second degree Jacobi (SDJ) method.